(untitled) (Práxis Educativa, 2017)
This article aims to discuss the concept of teacher professional development and its implication in the teacher education processes of Marcelo García (1999) and Oliveira-Formosinho’s (2009) studies. The following basic questions form the basis of the discussion: What teaching practices can contribute to the teacher development process? What reflections are necessary so that the work space, that is, the school and its specificities can participate in the professional development process of the teachers? The results of this conceptual reflection show the need to research and value the formative spaces of teachers, in order to prioritize mainly the intentionality of working on the personal dimension of the teacher in the formative spaces of teachers, whether initial or continuing teacher education. Keywords: Teacher professional development. Teacher education. Beliefs in teaching practice.